Is Money Really Green? - An Investigation Into Environmental Supply Chain Practices, with a Cost Focus - John Bancroft (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
In the setting of the supply chain and the environment, logistical operations are the most visible and contribute significantly to CO2 emissions (Dekker et al., 2011); Tol (2006) suggests that transportation accounts for 14% these emissions. As most products consumed have a global footprint it is important that logistics is managed with a green and cost effective approach. For third party logistics providers and in-house logistics operations to reduce CO2 emissions and "green up" their operations, it must be possible to do this whilst remaining competitive in areas such as cost, reliability and performance. Without this, it is unlikely that logistics providers will voluntarily make changes to their operations. This research paper will investigate current green initiatives as well as future approaches and evaluate them, focusing on those which can maintain or reduce costs whilst sustaining performance and reliability. Investment in environmentally friendly distribution practices has become a must for organisations; the degree to which this is practiced and invested in varies significantly. The motivation for this investment could be for numerous reasons; a genuine care for the environment, legislation, pressure from environmentalists or due to an increase in the cost of fossil fuels. For investment to be facilitated it must be sustainable fiscally, or these practices cannot be continued. Helper et al. (1997) and Conrad and Morrison (1989) suggest that previous attempts to reduce the impact of supply chain practices have frequently increased costs, thus discouraging investment in such practices.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; green; cost focus; reliability; performance